Symplocos deflexa - Tsen, S.; Matusin, D.; Damit, A.; Khoo, E.; Maryani, A.; Colin Ruzelion Maycock; Nilus, R.; Sugau, J.; Pereira, J.T. (International Union for Conservation of Nature and Natural Resources, 2021)
Symplocos deflexa is a small tree, endemic to Sabah. The estimated area of occupancy (AOO) and extent of occurrence (EOO) are 28 km2 and 34.5 km2, respectively. Majority of the records of this species are from Kinabalu Park, a protected area. There is no immediate threat to this species. Hence, it is assessed as Least Concern. Symplocos deflexa is endemic to Sabah, Malaysia. It is known from Tenompok, Mount Kinabalu and the local vicinity, Ranau.